In-depth understanding of 110-type domain walls in bismuth titanate ceramics. (August 2022) - Xie, Shaoxiong; Shi, Jikai; Xu, Qian; Wang, Qingyuan; Zhu, Jianguo; Sato, Yukio; Chen, Qiang
Abstract: Bismuth titanate(BIT) ceramics have been widely studied for high temperature applications thanks to their high Curie temperature and large spontaneous polarization. The underlying domain structures play significant roles in regulating the macroscopic properties of ferroelectric materials, while there is only limited knowledge of the domain structures for BIT ceramics until now, substantially bad for the development of BIT-based new materials. In this study, the intriguing domain walls(DWs) in BIT ceramics were investigated in detail. The atomic-scale observation reveals that there primarily exist energetically favorable 110-type 90° DWs in BIT ceramics. Combined with the theoretical analysis, these DWs are not only elaborated under multiple piezoelectric response modes, but also further corroborated by the quantitative reconstruction of spatial polarization distributions of twin-related ferroelectric variants. This work sheds insight into domain structure and piezoelectric response mechanism in BIT ceramics, and contributes to promoting their more applications in advanced electron devices. Graphical abstract: Image, graphical abstract